DEVELOPMENT OF PORTABLE AIR FILTER TEST SYSTEM USING PARTICULATE MATTER (PM) SENSOR - Ahmad Hapidin, Dian
Air filters have been utilized in many applications, such as vehicle cabin air filters, masks, air conditioning filters, and building ventilation filters. Due to many uses of the filters for daily basis, its fabrication and characterization technology have been extensively developed. The filter characterization can be done by measuring some filtration parameters, i.e. pressure drop, filtration efficiency, and quality factor. Due to the high demand to the filters, the assessment to those filtration parameters are needed with a lower test cost and a more accessible apparatus. Therefore, we developed a portable air filter test system, abbreviated as PAFT, which can be used to measure the filters pressure drop, filtration efficiency, and quality factor. The PAFT was built using two differential pressure sensors (TE Connectivity Measurement Specialties, GA100-015WD; and Sensirion, SDP1000-L05) for pressure drop measurements and a commercial particulate matter (PM) sensor (Sharp GP2Y1010AU0F) to measure the filtration efficiency. The implementation of PM sensor for air filter testing is a novel method in the field of filtration technology. The PM sensor is generally used to measure the mass concentration of particles for air pollution monitoring networks. In this study, however, the PM sensor was used to measure the particle number concentration before and after filtration to obtain the filter efficiency data. Therefore, for the implementation in the PAFT system, the PM sensor need to be evaluated and optimized. Some PM sensor characteristics, i.e. linearity, sensitivity, and output responses, were evaluated for the different sensor air flow rate, particle size and particle source. The experimental results show that the PM sensor air flow rate did not affect the sensor output response so that the flow rate can be selected according to the PAFT needs. The PM sensor output response was also tested using particle sources with varied diameters. The test results show that the sensor could not detect particles under 100 nm in size. In addition, the sensor output voltage terhadap particle diameter graph obtained from this test was also agree with Mie theory calculations, which predict the sensor response fluctuation for the particle sizes above 600 nm. PM sensors had different sensitivity to particle size and different PM2.5 sources. This related to the scattering intensity by particles, which depends on the particle physical parameters, such as size, refractive index, and material composition. Nevertheless, the PM sensor shows a very linear response to the particle number concentration for all test particles. PSL test particles with the sizes of 163, 216, 234 and 303 nm produced high sensor response linearity with the R2 of 0.9247, 0.9929, 0.9924 and 0.9983, respectively. The filtration efficiency is usually expressed as the ratio of the particle number concentration before and after filtration. In this study, filtration efficiency was expressed as the ratio of sensor output voltage. High sensor response linearity is important for efficiency measurement because it eliminated several parameters, such as particle density and sensor factors. The PAFT was calibrated by a standard air filter testing system that used a condensation particle counter (CPC) for filtration efficiency measurements. The calibration was carried out using nanofiber filters having various efficiencies. The calibration resulted in a filtration coefficient (Kf), which was then used to correct the efficiency value measured by the PM sensor. The PAFT was used to test the performance of some commercial mask products. The test results showed a good measurement results compared to reference efficiency with an average error of around 2.5%. The complete design of the portable air filter test system and experimental methods will be discussed in detail.